Biological Studies on the True Spider, Artema Atlanta Walckenaer, 1837 (Araneida: Pholcidae) When Fed On Different Prey Species (British Journal of Multidisciplinary and Advanced Studies, 2018)
Biological aspects of the spider species, Artema Atlanta Walckenaer, 1837 was studied at constant conditions in laboratory (25±2°C and 60-70% R.H.) when fed on four prey. larva of the vinegar fly, Dorsophila melanogaster and the fruit fly, Ceratitis capitata.were introduced to the first and second spiderlings, stored grain worm moth, Ephestia kuehniella and the vinegar fly, Dorsophila melanogaster introduced to the third and fourth spiderlings and house flies, Musca domestica, stored grain worm moth, Ephestia kuehniella and the vinegar fly, Dorsophila melanogaster introduced to the fifth and sixth spiderlings. Incubation period averaged 11.5 ± 1.20 days. The pre- oviposition period was 19.81 days before laying eggs, while the oviposition period averaged 32.8 ± 3.77days; the post- oviposition period averaged 134.9 ± 3.72 days. Moulting, copulation and feeding behaviour were also studied
Keywords: Araneida; Artema Atlanta Walckenaer; Biological Studies; True Spider